Spiritual Experiences and Integral Realization - Basu, Arabinda (Journal of Dharma, 1976)
Hinduism at its highest can very well be described as a record of the varieties of spiritual experiences and a most luminous guide to spiritual disciplines. In its basic scriptures we come across different statements of the nature of the supreme Reality. Theologians and philosophers not especially impressed by the validity of spiritual experience of a comprehensive nature find this baffling. Even those who have faith in the truth of the scriptures portraying the nature of the Reality in diverse manners, describing features of the Absolute in such a way that the statements seem to be mutually contradictory, try to emphasize one statement over the others. Their motive is philosophical consistency’ and from their point of view, they are justified. But in the process of building a foolproof metaphysical system based on spiritual experience, they sacrifice something, sometimes indeed a great deal of the variety and richness of spiritual experience. It is necessary to enquire into the structure, function and capacities of that in man who is capable of having spiritual experience. Equally it is incumbent on us to investigate the nature’ of spiritual experience as such, whether it does or does not outstep the boundaries of logical reason or whether it must conform to the canons of philosophical thinking.